Challenges in Management of Fournier’s Gangrene after the Perianal Abscess- A Case Report and Review of Literature - Shehi , Endrit; Andrea , Gjergj; Biberaj , Petrit; Dogjani, Agron (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Fournier’s Gangrene (FG) is a rare and potentially fatal form of necrotizing fasciitis that affects the perineal, perianal, or genital regions. The condition often originates from an infection in the anorectal or genitourinary area and is exacerbated by comorbidities, such as diabetes mellitus, chronic alcoholism, and immunosuppression. The rapid progression and high mortality associated with FG necessitate immediate diagnosis and prompt surgical intervention. CASE PRESENTATION: We present a case of a 52-year-old male with poorly controlled diabetes mellitus who developed FG following the drainage of a perianal abscess. Despite early surgical intervention, the infection progressed, leading to extensive necrosis of the perineum, scrotum, and lower abdominal wall. The patient required multiple debridement, broad-spectrum antibiotics, and intensive care management. Over a prolonged hospital stay, the patient recovered with significant wound care, including skin grafting, in large defect. This case illustrates the complexity of managing FG, mainly arising from a perianal abscess. The presence of diabetes mellitus complicates the clinical course and increases the risk of severe outcomes. A comprehensive multidisciplinary approach involving surgical, medical, and supportive care teams is essential for successful management. A review of the current literature highlights the critical importance of early and aggressive treatment to improve patient outcomes in FG cases. CONCLUSION: FG following a perianal abscess presents significant management challenges, especially in patients with underlying comorbidities. This case emphasizes the necessity of early diagnosis, prompt surgical intervention, and a multidisciplinary approach to care. Despite the severity of the condition, timely and comprehensive management can lead to favorable outcomes.